Multicultural World and Intercultural Challenge - Mesić, Milan, sociolog (2008)
Contrary to predictions of modernization theories since 19th century until recently - that the development of pre-modern into modern industrial societies entails demise of traditional particularistic, especially ethnic, identities – contemporary societies, primarily the most advanced ones, are faced with ethnic revival and other forms of social diversities seeking their public recognition .The general public awareness is growing that contemporary societies become more and not less culturally diverse than they used to be. It becomes more obvious within this framework that the ethno-cultural factors will play a crucially important role in shaping the social life of these nation-states well into the future. The author agrees with J. Banks in his argument that a multicultural (multiculturalist) society has to seek for a balance between diversity and unity. One of the challenges to diverse democratic nation-states is to provide opportunities for different groups to maintain aspects of their community cultures while building a nation in which these groups are structurally included and to which they feel allegiance. A delicate balance of diversity and unity should be an essential goal of democratic nation-states and of teaching and learning in democratic societies.